Diseño de un plan integral de manejo de residuos sólidos en la zona urbana del distrito de Olmos - Odar Salazar, Lucy Viviana (2023)
The objective of the research was the design of a comprehensive solid waste management plan for the urban area of the Olmos district. The research was applied and quasi-experimental, the sample was 80 homes, the techniques of surveys and direct observation were used; and as an instrument the questionnaire and bibliographic record. In the results, the management of the district's waste was evaluated, which resulted in a deficit in most of its processing stages. The per-capita generation was 0.4421 kg/inhab. The perspectives of the residents regarding the management of solid waste (SRM) in the home, it was appreciated that they carried out the minimum management from its generation to its final disposal; finding that there is no segregation or recycling at home. In the evaluation of knowledge about the MRS; Likewise, it was possible to appreciate that 55% have a clear and concise notion of what the MRS is; Likewise, they know about the impact that it can cause both to health and to the environment. It was concluded that the comprehensive solid waste management plan improves SWM and consists of four main activities: reinforcing the operational capacity of the municipality, increasing levels of awareness and environmental education, promoting reduction activities, reuse and recycling